Ergonomic practices and banking employee performance: A sequential explanatory approach - Karmacharya, Sadin; Bhattarai, Ujjwal; Timsina, Baburam; Shrestha, Nishesh; Tamang, Sanjita (American Journal of STEM Education, 2025)
Using the sequential explanatory method, this study sheds light on the influence of ergonomics practices on the performance of banking employees. Data from 267 banking employees were collected and analyzed Via PLS-SEM, and using Heidegger’s interpretative philosophy, a semi-structured interview was conducted purposively with seven frontline employees. The study found that cognitive and organizational ergonomics significantly predict employee performance, while environmental and physical ergonomics were not supported. Thematic analysis identified four major themes: physical ergonomics and comfort, environmental ergonomics and workspace design, cognitive ergonomics and mental workload, and organizational ergonomics and support systems. This study highlights the importance of cognitive and organizational ergonomics, challenging traditional ergonomic models and offering practical recommendations for optimizing work environments in customer-focused and knowledge-intensive industries.